2020
DOI: 10.18178/ijesd.2020.11.1.1222
|View full text |Cite
|
Sign up to set email alerts
|

Predicting River Pollution Using Random Forest Decision Tree with GIS Model: A Case Study of MMORS, Philippines

Abstract: This study aims to predict the pollution level that threatens the Marilao-Meycauayan-Obando River System (MMORS), located in the province of Bulacan, Philippines. The inhabitants of this area are now being exposed to pollution. Contamination of this waterway comes from both formal and informal industries, such as a used lead-acid battery, open dumpsites metal refining, and other toxic metals. Using various water quality parameters like Dissolved Oxygen (DO), Potential of Hydrogen (pH), Biochemical Oxygen Deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The results showed that the RF model outperformed the SMO-SVM model in most cases and had higher prediction accuracy for water quality indicators. Victoriano [24] used dissolved oxygen (DO), pH, biochemical oxygen demand (BOD), total suspended solids (TSS), nitrate, phosphate, and coliform as attribute values to construct a predictive model using the random forest decision tree algorithm. The model was applied to predict the pollution level of rivers in the MMORS River in Bulacan Province, Philippines.…”
Section: Random Forestmentioning
confidence: 99%
“…The results showed that the RF model outperformed the SMO-SVM model in most cases and had higher prediction accuracy for water quality indicators. Victoriano [24] used dissolved oxygen (DO), pH, biochemical oxygen demand (BOD), total suspended solids (TSS), nitrate, phosphate, and coliform as attribute values to construct a predictive model using the random forest decision tree algorithm. The model was applied to predict the pollution level of rivers in the MMORS River in Bulacan Province, Philippines.…”
Section: Random Forestmentioning
confidence: 99%
“…Random forest (RF): In 2001, Breiman introduced a random forest technique to categorise machine learning [34]. The random forest approach had a substantial influence on artificial intelligence, computer development and machine learning [35].…”
Section: Ensemble Regressionmentioning
confidence: 99%
“…The RF model predicted BOD better than the M5 model tree at Karun River in Ahvaz station, Iran (Golabi et al, 2020). Victoriano et al (2020) developed an RF‐based GIS model to forecast the Marilao‐Meycauayan‐Obando River System (MMORS)'s pollution level from coliform, phosphate, DO, TSS, nitrate, pH, and BOD in the province of Bulacan, Philippines.…”
Section: Introductionmentioning
confidence: 99%